Gender and Power Relation in Margaret Atwood's Novel The Handmaid's Tale - Khairunnisa Tambunan; Deliana Deliana; Rahmadsyah Rangkuti; Rahmah Fithriani; Alemina Br Perangin-angin; Nilma Zola (STKIP Singkawang, 2025)
This study examines the intersection of gender ideology and power relations in The Handmaid’s Tale, a novel by Margaret Atwood that portrays a dystopian society governed by patriarchal control. Employing Feminist Critical Discourse Analysis (FCDA) as the methodological framework, this research investigates how gender ideology is embedded and reproduced through the novel’s language and social structures. Specifically, the study addresses three research questions: (1) What elements of gender ideology are depicted in the novel? (2) How are gender ideology and power interrelated? (3) Why are these themes central to the narrative? Utilizing a qualitative approach, the analysis focuses on narrative and discursive elements to uncover representations of gender inequality and the systematic repression of women’s autonomy. The findings indicate that the novel reflects real-world patriarchal ideologies by illustrating how language and institutional norms uphold gendered power imbalances. This research contributes to feminist literary scholarship by demonstrating how literature can expose, critique, and resist oppressive social structures through discourse.